Features of case endings in the «Babyrnama» language - Khalmetov, А.Р.; Yeskeyeva, М.Қ.; Baimukhambetova, Э. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2025)
The Chagatai language was used by all Eastern Turkic peoples inhabiting vast territories from the 15th to the 20th century as a unified written language, and many valuable works were written in it. One such work is the Baburnama (15th-16th centuries) by Zahir ad-Din Muhammad Babur, the shah. Babur's creativity occupies a special place in the history of the Turkic peoples. This work is a source of Turkic culture and history, and also an important source that helps to understand the development path of modern Turkic written languages. The article presents a comparative analysis of the case endings and their functions in sentences in the Baburnama, based on data from other Turkic written monuments. A general description of the development of the case category in Turkic languages is provided, and the specific features of the case endings in the language of the Baburnama are identified. The grammatical meaning and functions of case endings in the language of written monuments, their ability to connect words in a sentence, and their role in ensuring syntactic relationships are discussed. The language of Zahir ad-Din Muhammad Babur's Baburnama is considered from the perspective of the early form of the Old Kazakh language.